Special Issue: Advances in SARS-CoV-2 Infection - Carlo Contini; John Charles Rotondo; Benedetta Perna; Matteo Guarino; Roberto De Giorgio (Microorganisms, 2023)
Coronavirus Disease 2019 (COVID-19) is a life-threatening disease caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus which was first reported in late 2019 in China, from where it then spread worldwide [...]